Additional file 17 of High density linkage maps, genetic architecture, and genomic prediction of growth and wood properties in Pinus radiata - Jules S. Freeman; Gancho T. Slavov; Jakob B. Butler; Tancred Frickey; Natalie J. Graham; Jaroslav Klápště; John Lee; Emily J. Telfer; Phillip Wilcox; Heidi S. Dungey (figshare, 2022)
Additional file 17: Table S5. Matrix of Pearson’s phenotypic correlation coefficients between growth and wood property traits analysed in the Pinus radiata QTL population. Two tailed P-values *P < 0.05, **P < 0.01, ***P < 0.001, ****P < 0.0001.
Keywords: Genetics